Study on Development of Composite Hydrogels With Tunable Structures and Properties for Tumor-on-a-Chip Research - Chen, Zaozao; Wang, Fei; Zhang, Jie; Sun, Xiaowei; Yan, Yuchuan; Wang, Yan; Ouyang, Jun; Zhang, Jing; Honore, Tess; Ge, Jianjun; Gu, Zhongze (Frontiers in Bioengineering and Biotechnology, 2020)
A major factor for developing new tumor models is to recreate a proper three-dimensional environment for 3D tumors culture. In this 3D microenvironment, extracellular matrices play important roles in regulation of hallmark features of cancer through biochemical and mechanical signals. The fabrication of a mechanical and biophysical controllable hydrogel, while sharing similarities with Matrigel in cancer invasiveness evaluation, is an urgent but unmet need. In this study, we developed a hybrid hydrogel system composed of GelMA and hydrolyzed collagen to model tumor micro-environment and tested with several cancer cells with different origin and characteristics. This hydrogel possesses a well-ordered homogenous microstructure, excellent permeability and an adjustable mechanical stiffness. This hydrogel demonstrated similar properties as Matrigel in tumor spheroids culture and 3D tumor invasiveness studies. It was further applied in a Tumor-on-a-Chip system with 3D-bioprinting. Our research demonstrated this hydrogel's effectiveness in tumor 3D culture, and its potential to replace Matrigel in cancer invasiveness evaluation.